2010
DOI: 10.1515/hf.2010.100
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of water vapour sorption of oleo-thermal modified wood of Acacia mangium and Endospermum malaccense by a parallel exponential kinetics model and according to the Hailwood-Horrobin model

Abstract: Two Malaysian hardwoods, acacia (Acacia mangium Wild.) and sesendok (Endospermum malaccense Bent. ex Müll. Arg.) that had been previously subjected to oleo-thermal modification, were studied to determine their dynamic sorption kinetic behaviour. All specimens were thermally modified in palm oil at 180°C, 200°C, and 220°C and 3 h treatment time. Data were analysed using the parallel exponential kinetics (PEK) model, and excellent fits to the experimental data were obtained. The relation between the monolayer wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
2
6

Year Published

2012
2012
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 8 publications
0
16
2
6
Order By: Relevance
“…The H-H model was two hydrate and the fitted coefficients of the model were not explicitly presented. Therefore, it was not possible to compare the present results with the findings reported by Jalaludin et al (2010a) . However, some similarities were found when analyzing the influence of the TM temperature on the accessibility of the primary sorption sites as Jalaludin et al (2010a) found a distinct reduction in monolayer water content after TM.…”
Section: Resultscontrasting
confidence: 73%
See 1 more Smart Citation
“…The H-H model was two hydrate and the fitted coefficients of the model were not explicitly presented. Therefore, it was not possible to compare the present results with the findings reported by Jalaludin et al (2010a) . However, some similarities were found when analyzing the influence of the TM temperature on the accessibility of the primary sorption sites as Jalaludin et al (2010a) found a distinct reduction in monolayer water content after TM.…”
Section: Resultscontrasting
confidence: 73%
“…The results show that the TM-induced changes are related only to the monomolecular sorption, which directly depends on the accessibility of the primary sorption sites. Jalaludin et al (2010a) applied the H-H model for analyzing the sorption isotherms of thermally modified and unmodified wood of two Malaysian species. The H-H model was two hydrate and the fitted coefficients of the model were not explicitly presented.…”
Section: Resultsmentioning
confidence: 99%
“…This also explains why samples conditioned for longer times after a change in RH exhibit slower rate of sorption as observed by Christensen and Hergt (1969). Due to the two-stage nature of the sorption process, it has often been analysed by the parallel exponential kinetics (PEK) model featuring two moisture sorption processes (fast and slow exponentials) using data for both untreated ) and modified wood (Hill et al 2012a;Himmel and Mai 2016;Jalaludin et al 2010a;Popescu et al 2014;Xie et al 2010). It may be difficult to compare the results across studies due to differences in sample mass and geometry as diffusion into the sample at some point becomes relevant, at least in the low-RH regime (Christensen 1965).…”
Section: Automated Sorption Balancesmentioning
confidence: 99%
“…As can be observed (by comparing with the data of Table 1), the hysteresis decreases with increasing surface area, the Bc-d sample showing almost no hysteresis. Mild thermal modification of wood has been shown to lead to an increase in sorption hysteresis [13]. This increase in hysteresis has been explained as being due to an increase in matrix stiffness, resulting in a higher T g for the thermally modified wood.…”
Section: Sorption Hysteresismentioning
confidence: 99%